2020
DOI: 10.3390/molecules25020242
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anthelmintic Activity of Saponins from Medicago spp. Against Sheep Gastrointestinal Nematodes

Abstract: Gastrointestinal strongyle nematodes (GIS) are included among the most important parasites of small ruminants. The widespread drug resistance and drug residues in products of animal origin have increased the interest in the search for natural compounds with anthelmintic activity as a valid alternative to current synthetic drugs. The aim of the present investigation was to test the ‘in vitro’ anthelmintic activity of saponins and prosapogenins from different Medicago species, selected for their importance as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Saponins were acknowledged for a wide range of biological activities, including a cytotoxic, antibiotic, anti-inflammatory and molluscicidal activity [8,9]. In addition, a high anthelmintic activity against gastrointestinal nematodes from donkey [10] and goats [11] was also proved for alfalfa (Medicago sativa L.) saponin mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Saponins were acknowledged for a wide range of biological activities, including a cytotoxic, antibiotic, anti-inflammatory and molluscicidal activity [8,9]. In addition, a high anthelmintic activity against gastrointestinal nematodes from donkey [10] and goats [11] was also proved for alfalfa (Medicago sativa L.) saponin mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Citral and lemonene (Macedo et al ., 2010), linalool and carvacrol (Zhu et al ., 2013), essential oil (Armstrong et al ., 2013), carvacrol (Andre et al ., 2016), thymol, carvacrol and eugenol (Hernando et al ., 2019), triterpenoids identified as urs-19(29)-en-3-yl acetate, (3 β )-Urs-19(29)-en-3-ol and 1-(2’,5’-dimethoxy phenyl)-glycerol (Cavalcante et al ., 2016), triterpenoid glycosides (saponins) identified as joazeiroside B and lotoside A (Gomes et al ., 2016) were some of the related compounds. Besides, other saponins revealed the presence of in vitro anthelmintic activity against nematodes eggs of goat (Botura et al ., 2013; Santos et al ., 2018), donkey (Maestrini et al ., 2019), sheep (Maestrini et al ., 2020) and L 3 of goat (Santos et al ., 2018). In a similar way, β -sitosterol steroid demonstrated anthelmintic activity against Ascaris suum (Villaseñor et al ., 2002) and sheep gastrointestinal nematodes (Giovanelli et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another most recent study found a significant inhibition of hatchability of H. contortus eggs with the use of saponins extracted from forage plants of 'Medicago' species (Maestrini et al 2020). The sheep experimentally infected with H. contortus and supplemented with yeast Saccharomyces cerevisiae for a period of 49 days showed a significant reduction of larvae and a higher number of circulating antibodies (Pinto et al 2020).…”
Section: Non-conventional Compoundsmentioning
confidence: 98%